The effect of exercise on high-level mobility in individuals with neurodegenerative disease: a systematic literature review. (March 2020) - Smith, Moira; Barker, Ruth; Williams, Gavin; Carr, Jennifer; Gunnarsson, Ronny
Abstract: Objective: To investigate the effect of exercise on high-level mobility (i.e. mobility more advanced than independent level walking) in individuals with neurodegenerative disease. Data sources: A systematic literature search was conducted in Medline, CINAHL, Scopus, SportDiscus and PEDro. Study selection: Randomised controlled trials of exercise interventions for individuals with neurodegenerative disease, with an outcome measure that contained high-level mobility items were included. High-level mobility items included running, jumping, bounding, stair climbing and backward walking. Outcome measures with high-level mobility items include the High Level Mobility Assessment Tool (HiMAT); Dynamic Gait Index; Rivermead Mobility Index (RMI) or modified RMI; Functional Gait Assessment and the Functional Ambulation Category. Study appraisal: Quality was evaluated with the Cochrane Risk of Bias Tool. Results: Twenty-four studies with predominantly moderate to low risk of bias met the review criteria. High-level mobility items were included within primary outcome measures for only two studies and secondary outcome measures for 22 studies. Eight types of exercise interventions were investigated within which high-level mobility tasks were not commonly included. In the absence of outcome measures or interventions focused on high-level mobility, findings suggest some benefit from treadmill training for individuals with multiple sclerosis or Parkinson's disease. Progressive resistance training for individuals with multiple sclerosis may also be beneficial. With few studies on other neurodegenerative diseases, further inferences cannot be made. Conclusion: Future studies need to specifically target high-level mobility in the early stages of neurodegenerative disease and determine the impact of high-level mobility interventions on community participation and maintenance of an active lifestyle. Systematic review registration number PROSPERO register for systematic reviews (registration number: CRD42016050362).